Extracorporeal Membrane Oxygenation for Respiratory Failure. (May 2020) - Quintel, Michael; Bartlett, Robert H.; Grocott, Michael P. W.; Combes, Alain; Ranieri, Marco V.; Baiocchi, Massimo; Nava, Stefano; Brodie, Daniel; Camporota, Luigi; Vasques, Francesco; Busana, Mattia; Marini, John J.; et al.
Abstract : This review focuses on the use of veno-venous extracorporeal membrane oxygenation for respiratory failure across all blood flow ranges. Starting with a short overview of historical development, aspects of the physiology of gas exchange ( i.e., oxygenation and decarboxylation) during extracorporeal circulation are discussed. The mechanisms of phenomena such as recirculation and shunt playing an important role in daily clinical practice are explained. Treatment of refractory and symptomatic hypoxemic respiratory failure ( e.g., acute respiratory distress syndrome [ARDS]) currently represents the main indication for high-flow veno-venous-extracorporeal membrane oxygenation. On the other hand, lower-flow extracorporeal carbon dioxide removal might potentially help to avoid or attenuate ventilator-induced lung injury by allowing reduction of the energy load ( i.e., driving pressure, mechanical power) transmitted to the lungs during mechanical ventilation or spontaneous ventilation. In the latter context, extracorporeal carbon dioxide removal plays an emerging role in the treatment of chronic obstructive pulmonary disease patients during acute exacerbations. Both applications of extracorporeal lung support raise important ethical considerations, such as likelihood of ultimate futility and end-of-life decision-making. The review concludes with a brief overview of potential technical developments and persistent challenges. Abstract : This review presents an overview of selected aspects of extracorporeal membrane oxygenation use in respiratory failure, including historical and technical development, relevant principles of gas exchange, clinical applications and indications, ethical considerations, and potential improvements for its optimal implementation.